The global prevalence of Spirometra parasites in snakes, frogs, dogs, and cats: A systematic review and meta‐analysis. Issue 6 (9th September 2022) - Badri, Milad; Olfatifar, Meysam; KarimiPourSaryazdi, Amir; Zaki, Leila; Madeira de Carvalho, Luis Manuel; Fasihi Harandi, Majid; Barikbin, Fatemeh; Madani, Parisa; Vafae Eslahi, Aida
Abstract: Background: Spirometra infection is aneglected food‐ and waterborne disease with worldwide distribution. Objectives: The present study aims to estimate the global prevalence of Spirometra species in snakes, frogs, dogs and cats. Methods: Multiple databases (PubMed, Scopus, ProQuest, Web of Science and Google Scholar) were searched for relevant literatures published up to March 2022. Results: Among 131 data sets (including 113 articles) that met the inclusion, 15 investigations reported Spirometra infection in snakes, 23 in frogs, 41 in dogs and 52 in cats. The pooled prevalence (95% confidence interval) in intermediate hosts and definitive hosts was found to be 0.313% and 0.089%, respectively. Based on continent, the infection was most prevalent in Asia for studies on snakes (0.696%) and frogs (0.181%), while Africa (0.224%) and Oceania (0.203%) were the regions with the highest pooled prevalence rates of the infection in dogs and cats, respectively. Among different diagnostic methods, the highest pooled prevalence was related to morphological method for studies on snakes, frog and cats with rate of 0.665%, 0.189% and 0.104%, respectively. Regarding studies on dogs, the highest pooled prevalence was observed for molecular technique (0.101%). Conclusions: The results presented here revealed the importance of establishing a prevention and control measure focused on protection of aquaculture systems from being contaminated with faeces of dogs and cats, and raising awareness of parasitic zoonotic diseases to decrease the transmission risk. Abstract : Spirometra species have been considered as neglected helminths in snakes, frogs, dogs and cats with a more recent growing interest in understanding its prevalence, means for prevention and better treatment, and the phylogenetic relationship of Spirometra in its various hosts. To build on our understanding of the epidemiology of Spirometra. The review and meta‐analysis in the submitted manuscript will contribute to filling this gap in knowledge.